Examining the Relationship Between Alcohol‐Energy Drink Risk Profiles and High‐Risk Drinking Behaviors. (25th March 2013) - Varvil‐Weld, Lindsey; Marzell, Miesha; Turrisi, Rob; Mallett, Kimberly A.; Cleveland, Michael J.
Abstract : Background: The mixing of alcohol and energy drinks (AMEDs) is a trend among college students associated with higher rates of heavy episodic drinking and negative alcohol‐related consequences. The goals of this study were to take a person‐centered approach to identify distinct risk profiles of college students based on AMED‐specific constructs (expectancies, attitudes, and norms) and examine longitudinal associations between AMED use, drinking, and consequences. Methods: A random sample of incoming freshmen ( n = 387, 59% female) completed measures of AMED use, AMED‐specific expectancies, attitudes, and normative beliefs, and drinking quantity and alcohol‐related consequences. Data were collected at 2 occasions: spring semester of freshmen year and fall semester of sophomore year. Results: Latent profile analysis identified 4 subgroups of individuals: occasional AMED, anti‐AMED, pro‐AMED, and strong peer influence . Individuals in the pro‐AMED group reported the most AMED use, drinking, and consequences. There was a unique association between profile membership and AMED use, even after controlling for drinking. Conclusions: Findings highlighted the importance of AMED‐specific expectancies, attitudes, and norms. The unique association between AMED risk profiles and AMED use suggests AMED use is a distinct behavior that could be targeted by AMED‐specific messages included in existing brief interventions for alcohol use.